KEPEMIMPINAN KEPALA SEKOLAH DALAM PENYELENGGARAAN PERPUSTAKAAN SEKOLAH - Nurhalisma, Lisna; Silvana, Hana (Universitas Pendidikan Indonesia, 2014)
AbstractA principal is the highest leader in school. The operation of school library is not separated from the principal leadership. This study aimed to investigate the principal leadership of SMAN 10. The principal management was measured by the leading indicators which include decision-making, communicating, motivating, selecting people and developing people with the use of management theory of Lewis A. Allen. The organization of school library was measured through the indicators of service, collections, and budget. The population of this study was students of SMAN 10 Bandung, with a sample of 95 people. This study used descriptive method with quantitative approach. The data was collected using closed questionnaire and interview. Based on the results of data analysis, it was found that principal leadership make a positive contribution to the school organization. Broadly speaking, the principal management of SMAN 10 Bandung is in good category. The test results of principal management in school library organization show that the leading indicators are in the moderate category.Keywords: leadership, school library, principal managementAbstrakKepala Sekolah adalah pimpinan tertinggi yang berada di sekolah. Penyelenggaraan perpustakaan sekolah tidak terlepas dari kepemimpinan Kepala Sekolah. Penelitian ini bermaksud untuk mengetahui Kepemimpinan Kepala Sekolah di SMAN 10 Bandung. Manajemen kepala sekolah diukur melalui indikator leading yang terdiri dari pengambilan keputusan, pengkomunikasian, pemberian motivasi, penyeleksian orang-orang dan pengembangan orang-orang dengan menggunakan teori manajemen dari Lewis A.Allen. Penyelenggaraan perpustaka sekolah diukur melalui indikator layanan, koleksi dan anggaran. Populasi dalam penelitian ini adalah siswa SMAN 10 Bandung, dengan sampel 95 orang. Metode penelitian menggunakan metode deskriptif dengan pendekatan kuantitatif. Teknik pengumpulan data menggunakan angket tertutup dan wawancara. Berdasarkan hasil analisis data diketahui kepemimpinan Kepala Sekolah memberikan kontribusi positif pada penyelenggaraan Sekolah. Secara garis besar manajemen Kepala Sekolah SMAN 10 Bandung termasuk dalam kategori baik. Hasil pengujian terhadap manajemen Kepalab Sekolah terhadap penyelenggaraan Perpustakaan Sekolah menunjukkan indikator leading berada dalam kategori sedang.Kata Kunci: Kepemimpinan, Perpustakaan Sekolah, manajemen kepala sekolah